Acoustical spectroscopy of carbohydrate aqueous solutions: saccharides; alkyl glycosides; cyclodextrins. Part I. Conformer variations - Udo KAATZE (Archives of Acoustics)
Acoustical attenuation spectra in the frequency range 12 kHz - 2 GHz and non-equilibrium time domain measurements are briefly reviewed for aqueous solutions of various mono- and disaccharides as well as alkyl glycosides. Several relaxation regimes emerge with relaxation times between 10-11s and 103s. In this paper relaxation terms reflecting conformational changes are discussed, particularly mutarotation (103s), chair-chair ring inversion (1 μs), two modes of pseudorotation (100 ns, 10 ns), disaccharide ring isomerisation (10 ns), and exocyclic side group rotation (1 ns).